TAKWÎN AL-MUṢṬALAHÂT AL-‘ARABIYYAH AL-HADÎTHAH FÎ MAJALLI ‘ILMI AL-DIBLÛMÂSIYYAH: Pembentukan Istilah Arab Modern dalam Bidang Ilmu Diplomasi - Ramdani, Fahmi; Masruroh, Emas; Yudhistira, Dadang (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
A diplomat needs to learn diplomatic terms, especially the acquisition of Arabic terms in the field of diplomacy. This research aims to understand the origin of the formation of diplomatic terms in the Arabic language. This research is of a descriptive qualitative type. The data collection method used in this research is the document analysis method. The primary sources are books on the science of diplomacy to extract its terms, books on morphology and arabization to understand and explain the origin of the terms, and dictionaries. Secondary sources include various related journals. The results show that the formation of terms in this research involves two processes: the morphological process and the arabization process. The morphological process involves transforming word forms from one form to another to achieve the desired meaning. The arabization process involves two possibilities: first, incorporating foreign language words into Arabic to become part of the Arabic language, the second possibility is incorporating modern foreign language words into Arabic using the Arabic word itself.